Facial features and social attractiveness: preferences of Bosnian female students - Bosankić, Nina; Besevic, Viktorija; Draganović, Selvira; Mesic, Enisa; Sokolovic, Suajb (Journal of Education Culture and Society, 2020)
This research aimed at testing multiple fitness hypothesis of attraction, investigating relationship between male facial characteristic and female students' reported readiness to engage in various social relations. A total of 27 male photos were evaluated on five dimensions on a seven-point Likert-type scale ranging from -3 to 3, by convenient sample of 90 female students of University of Sarajevo. The dimensions were: desirable to date – not desirable to date; desirable to marry – not desirable to marry; desirable to have sex with – not desirable to have sex with; desirable to be a friend – not desirable to be a friend; attractive - not attractive. Facial metric measurements of facial features such as distance between the eyes, smile width and height were performed using AutoCad. The results indicate that only smile width positively correlates with desirability of establishing friendship, whilst none of the other characteristics correlates with any of the other dimensions. This leads to the conclusion that motivation to establish various social relations cannot be reduced to mere physical appearance, mainly facial features, but many other variables yet to be investigated.